SOSIALISASI PENGGUNAAN MODUL LINUMERASI PADA SISWA SEKOLAH MENENGAH PERTAMA - Febriana, Rina (Gemi: Jurnal Penelitian dan Pengabdian, 2022)
Learning media serves to guide the learning process. The availability of adequate learning media will assist educators in carrying out the learning process to achieve the expected learning goals and achievements. Good learning media should provide opportunities for students to actively build their knowledge. The learning media used in the learning process are still minimal and even seem to be neglected. Education is not only a medium for transferring knowledge but also a medium for developing students' critical thinking. The current demands of education are not only to form competitive learners but also to be able to face future challenges that play a role in changing society for the better. In facing the era of the industrial revolution 4.0 and the era of society 5.0, a new perspective in the field of education is needed that can produce graduates according to the times. To be able to produce graduates who are following the demands of changing times, a strong foundation in learning in schools is needed in the form of literacy and numeracy. A solid foundation in literacy and numeracy is essential for every elementary school student to support their ability to engage in education, reach their potential, and participate fully in society. Therefore, it is necessary to introduce students to learning about numeration. Numerical literacy is the knowledge and skill to use various kinds of numbers and symbols related to basic mathematics to solve practical problems in various contexts of everyday life and analyze information that is displayed in various forms and then uses the interpretation of the results of the analysis to predict and draw conclusions decision